Independent bodies specialized in ensuring the principle of participation in the federal system Study under the permanent Iraqi constitution for 2005 - چواس حسن رسول (QALAAI ZANIST JOURNAL, 2019)
The Constitution of Iraq in 2005 has restructured the Iraqi state in accordance with two main and interrelated demands for the Iraqis, namely the democratization and federalism of the Iraqi state. The constitutional legislator resorted to many principles, institutions and procedures to achieve the two previous demands. Among these institutions that the Constitution required to be established are the Independent Commissions, Some of These Independent commissions related to technical issues and others concerned with the democratization of the state. Two of them were dedicated to the new federalism of Iraq, by ensuring the realization and application of one of the main principles of the federal state which is the principle of participation, these two Independent Commissions are (The Public Commission of Guarantee the rights of regions and governorates that are not organized in the region) which provided for in Article (105) of the Constitution and (The Public Commission of auditing and appropriation of federal revenues) which provided for in Article (106) of the Constitution. This study will examine these two Commissions and deal with them in all their aspects in light of both the Iraqi Constitution and the laws governing them, and marking down our observations on the law and propose what we consider necessary amendments for the purpose of development, due to their importance for the new phase of the Iraqi state